2019
DOI: 10.9734/ejnfs/2019/v9i230053
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Contamination and Potential Human Health Risk via Consumption of Vegetables from Selected Communities in ONELGA, Rivers State, Nigeria

Abstract: Background: Anthropogenic activities such as excessive oil exploration, automobile emissions with agricultural activities, etc tend to elevate the concentrations of heavy metals in the soil. These metals are accumulated by plant roots, thereby resulting to heavy metal contamination of such plants. Objectives: This study evaluated the concentration of heavy metals namely: Lead (Pb), Cadmium (Cd), Nickel (Ni), Arsenic (As), Iron (Fe), and Copper (Cu) in edible vegetables from selected communities in Ogba/E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…"The range of ILCR and ∑ILCR from consumption of all the evaluated samples as highlighted above, which raises the level of health concern for the consumer population as they may contribute to the population cancer burden is similar" to what was reported by Gebeyehu and Bayissa [45], in vegetables from Mojo Ethiopia, the ILCR and ∑ILCR reported from consumption meat and sea food samples from Xiamen, China [57]. The ILCR and ∑ILCR in Vegetables from Pearl River Delta South China [58], in fruits and vegetables from Jamaica [59], in vegetables from a Pb/Zn smelter in Central China [60] in vegetables grown in Patuakhali province Bangladesh [61] and in fruit, root and leafy vegetables, and fruits in a study conducted in a sub urban industrial area of Bangladesh [47].are also in line with the result of the present study. But the results differ from the results for vegetables from some selected communities from ONELGA Rivers State, Nigeria that reported non carcinogenic cancer risks from the vegetable samples in the study [62].…”
Section: Discussionsupporting
confidence: 77%
“…"The range of ILCR and ∑ILCR from consumption of all the evaluated samples as highlighted above, which raises the level of health concern for the consumer population as they may contribute to the population cancer burden is similar" to what was reported by Gebeyehu and Bayissa [45], in vegetables from Mojo Ethiopia, the ILCR and ∑ILCR reported from consumption meat and sea food samples from Xiamen, China [57]. The ILCR and ∑ILCR in Vegetables from Pearl River Delta South China [58], in fruits and vegetables from Jamaica [59], in vegetables from a Pb/Zn smelter in Central China [60] in vegetables grown in Patuakhali province Bangladesh [61] and in fruit, root and leafy vegetables, and fruits in a study conducted in a sub urban industrial area of Bangladesh [47].are also in line with the result of the present study. But the results differ from the results for vegetables from some selected communities from ONELGA Rivers State, Nigeria that reported non carcinogenic cancer risks from the vegetable samples in the study [62].…”
Section: Discussionsupporting
confidence: 77%
“…The risk assessment for carcinogenic exposure effect has revealed that the incremental lifetime cancer risk (ILCR) and the cumulative lifetime cancer risks (∑ILCR) were all within the safe limit for cancer in the children and the adults population for all the vegetable samples evaluated (Tables 6 and 7). The results are similar to the results for vegetables from some selected communities from ONELGA Rivers State, Nigeria that reported non carcinogenic cancer risks from the vegetable samples in the study (Ogbo and Patrick-Iwuanyanwu, 2019), but differ from carcinogenic risk vegetables reported in earlier studies from Katsina state, Nigeria (Yaradua et al, 2019a, b;Yaradua et al, 2020).…”
Section: Resultssupporting
confidence: 87%
“…Studies have shown that Fe is the predominant metal in the soil of Southeast ecological region of Nigeria [31]. Activities of welders and the wind [25] effect in the dispersion of the ferralitic soil to several locations including the classrooms can contribute to Fe pollution in the environment. Iron is one of the essential metals for humans.…”
Section: Metal Concentrationsmentioning
confidence: 99%